From police violence to (self) censorship: mapping the continuum of criminalization of student-led Palestine solidarity activism in the Netherlands - Pali, Brunilda (Criminological encounters, 2025)
This article explores the criminalization of student-led solidarity activism in the Netherlands. Self-identified as the “student intifada” this activism has taken place in university campuses around the world including in the Netherlands and has faced varying levels of criminalization. Through applying a criminalization lens to the student intifada in the Netherlands the article asks questions such as: Through what processes are political ideologies, movements, and acts of resistance, such as BDS campaigns, studentled protests, and broader forms of solidarity, constructed as criminal by political, legal, and institutional actors? What mechanisms, discourses, and tactics are mobilized to suppress these forms of activism, and why? Why is solidarity with Palestinians so often met with accusations of terrorism, antisemitism, or threats to public order and security? And what are the broader implications of this repression, not only for freedom of expression, assembly, and association, but also for the future of political solidarity and resistance itself? In answering these questions, the article employs a “criminalization continuum” lens in documenting the various forms criminalization of solidarity with Palestine has taken in the Netherlands, from arrests and police violence to surveillance, censorship, and stigmatization. Such measures not only mirror the broader global crackdown on political dissent more generally, and on Palestine solidarity activism in particular, but also reflect and reinforce the criminalization of Palestinian resistance itself. We argue that such tactics undermine the democratic principles that universities claim to uphold and perpetuate a culture of intimidation, fear and apathy that endangers critical engagement and solidarity, and call for an urgent and critical evaluation of how universities, governments, and societies at large respond to pro-Palestinian activism, arguing that the criminalization of the student intifada is a litmus test for academic freedom, democracy, and justice.